Do Social & Psychological Factors Affect Investment Intention in Islamic Capital Markets? - Fachmi Pachlevi Yandra; Dwi Marlina Wijayanti (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
This research aimed to predict social and psychological factors affecting individual investment decision in the Islamic capital market. Furthermore, the Theory of Planned Behavior Model (TPB) was used to explain irrational investor decisions affected by cognitive biases. We attempted to correct the pessimistic view of investors on the Islamic capital market using social & psychological perspectives. This study used a self-administered survey and obtained 82 investors and non-investors as respondents. The main criteria of individuals selected as respondents of the study were those who knew about the stock market and have heard the term Islamic capital market. This paper provided empirical insights on how the TPB model successfully explains the variance of change in investment intention. The results indicated that all predictors had a significant positive effect on individual investment intention. Individuals tend to exhibit a cognitive bias that lead to irrational decisions because individual’s attitude and PBC shape false perception of the usefulness of the Sharia capital market.